Perceived sensitivity to medicines and the experience of side-effects: understanding intentional medication nonadherence among people living with HIV. Issue 10 (26th November 2022) - Kalichman, Seth C.; Katner, Harold; Hill, Marnie; Ewing, Wendy; Kalichman, Moira O.
ABSTRACT: Patient initiated decisions to forgo taking medications (i.e. intentional nonadherence) pose significant challenges to managing chronic health conditions. Identifying factors and their underlying mechanisms that impede medication adherence is essential to designing treatment improvement interventions. This study tested a conceptual model that posits the effects of perceived sensitivity to medicines on adherence can be explained by the experience of side-effects, leading to intentionally nonadherent behaviors. Patients receiving HIV care in the southern United States (N = 209) completed measures of perceived sensitivity to medicines, antiretroviral therapy (ART) side-effects, intentional nonadherence and overall adherence. Patients also provided consent to access their electronic medical records to collect subsequent reports of HIV viral load tests. Results indicated that more than one in four participants were intentionally nonadherent to ART. Mediation modeling showed that perceived sensitivity to medicines was associated with greater experience of ART side-effects and intentional nonadherence, which impacted overall ART adherence and HIV viral load. There were also significant indirect effects of perceived sensitivity to medicines on HIV viral load through side-effects and intentional nonadherence. Patients with increased perceived sensitivity to medicines are at risk for poor treatment outcomes and these negative outcomes are partly explained by experiencing greater side-effects and intentional nonadherence.